Handbook of research on artificial intelligence techniques and algorithms - Vasant, Pandian (Hershey, PA : Information Science Reference, an imprint of IGI Global, 2015)
'This book highlights the cutting edge developments in the promising research area of artificial intelligence, applying Meta-heuristics Optimization (MO) Techniques to real world problems in a variety of fields including business, logistics, computer science, engineering, and government'--
Includes bibliographical references and index.
Keywords: Artificial intelligence; Algorithms